Wood quality assessment of rubberwood : The effect of clone and age on specific gravity and strength properties / Suhaimi Muhammed, Mansur Ahmad and Mohd Hamami Sahri - Muhammed, Suhaimi; Ahmad, Mansur; Sahri, Mohd Hamami (Universiti Teknologi MARA Cawangan Pahang, 2001)
Specific gravity and strength properties were determined for rubberwood (Hevea brasiliensis) from two clones (RRIM600 and RRIM623) and two age groups (22 years and 35 years). The specific gravity was higher for clone RRIM600 compared to clone RRIM623 and no difference between near pith and near bark. Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) showed no significant difference between the two clones although clone RRIM600 exhibited higher MOE values. The Maximum Compression Strength (MCS) was higher for clone RRIM600 and Maximum Shear Strength (MSS) was higher for clone RRIM623. Among age group, the 22-year old trees exhibited higher values for both MCS and MSS. It is hoped that the values for specific gravity and strength properties derived from this study can be a beneficial guide in assessing the suitability of rubberwood for specific application.